New record of the species Spongilla lacustris L. (Porifera) (Baghdad Science Journal, 2004)
The species Spongilla lacustris was identified for the first time in Iraq, it was found during winter 1998 in an irrigation canal within the campus of the University of Baghdad (Jadiriah), water is drawn from Tigris river. The specimens were found in water samples of sizes ranging between 5-50 cm with yellowish color . It was found in two habitats , one as attached on submerged aquatic plant Ceratophyllum sp., and the other on the canal bottom (concret material). Some physico- chemical characters were determined including conductivity ,salinity , pH, total alkalinity, total hardness, Ca ,Mg ,anddissolved oxygen. Water quality was fresh , alkaline, hard and well aerated.